Biased Health Perceptions and Risky Health Behaviors: Theory and Evidence - Patrick Arni; Davide Dragone; Lorenz Götte; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2020)
This paper investigates the role of biased health perceptions as driving forces of risky health behavior. We define absolute and relative health perception biases, illustrate their measurement in surveys and provide evidence on their relevance. Next, we decompose the theoretical effect into its extensive and intensive margin: When the extensive margin dominates, people (wrongly) believe they are healthy enough to "afford" unhealthy behavior. Finally, using three population surveys, we provide robust empirical evidence that respondents who overestimate their health are less likely to exercise and sleep enough, but more likely to eat unhealthily and drink alcohol daily.
Keywords: C93; D03; D83; I12; 330; health bias; health perceptions; subjective beliefs; overconfidence; underconfidence; overoptimism; risky behavior; smoking; obesity; exercising; SF12; SAH; BASE-II